URGENSI KELAS LITERASI INFORMASI BAGI MAHASISWA DI PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH GOMBONG - Sundariyati, Dwi (Publication Library and Information Science, 2023)
This article aims to determine the urgency of the information literacy class for students at the Universitas Muhammadiyah Gombong library. The development of information technology is no longer evolving, but it has become a mighty information revolution. For that, it takes the ability to filter out all the available information. The library is a provider and manager as well as an information ride, so librarians play an important role in providing information search guidance needed by librarians or students, the research method used a qualitative descriptive method by examining in depth a problem. The Collected data Techniques were interviews and literature studies. Interviews are conducted with student respondents, lecturers, and librarians. From the results of the study, it can be concluded that students need assistance and guidance in doing information literacy, so it needs to be held or held in an information literacy class. It is an effort of the library in providing information literacy services. The library in collaboration with the study program requires students to attend classroom literacy lectures. In this information literacy activity, the theme delivered adjusts to the needs of students, literacy themes that have been carried out include:1} e-journal search 2) Mendeley reference management, 3) plagiarism and 4) online presentation media.